2021
DOI: 10.1016/j.ajic.2020.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of dry hydrogen peroxide on reducing environmental microbial bioburden risk in a pediatric oncology intensive care unit

Abstract: Background: Routine manual cleaning and disinfection of the health care environment is often suboptimal. Residual contamination poses an infection risk, particularly for immunocompromised patients. This study evaluates the efficacy of dry hydrogen peroxide (DHP) on microbial surface contamination in a pediatric oncology intensive care unit. Methods: Surface samples from 5 high-touch and 2 low-touch surfaces were obtained for culture and adenosine triphosphate readings after manual cleaning on multiple days in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Our study provides the rst evidence for the virucidal activity of DHP, which has mainly been validated for the inactivation of human bacterial pathogens in the past 15 . The outcome further justi es the evaluation of DHP in inactivating other enveloped RNA viruses that are transmitted through contaminated surfaces.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our study provides the rst evidence for the virucidal activity of DHP, which has mainly been validated for the inactivation of human bacterial pathogens in the past 15 . The outcome further justi es the evaluation of DHP in inactivating other enveloped RNA viruses that are transmitted through contaminated surfaces.…”
Section: Discussionmentioning
confidence: 85%
“…The rst laboratory was charged with DHP by allowing the continuous operation of a Sentry DHP generator at full output of 38 cubic feet per minute (Synexis LLC, Lenexa, KS) for 24 hours prior to the experiment. This setting generates DHP at a concentration no greater than 25 parts per billion (ppb) 15 .The second laboratory was used as a control environment which maintained the negative air pressure required for BSL-3 laboratories. To simulate the air exchange conditions in public spaces, the rate of air exchange in both BSL-3Ag laboratories was reduced to seven air exchanges per hour, the minimal frequency required for the maintenance of negative air pressure.…”
Section: Methodsmentioning
confidence: 99%
“…These results align with previous research demonstrating statistically significant reductions in surface microbial bioburden with use of DHP™ as an adjunct to standard manual cleaning protocols. 36,37 Further, a recent study of DHP™ in a pediatric oncology intensive care unit demonstrated reductions in both air and surface contamination along with a robust safety profile. 37 In the present study, DHP™ resulted in an overall 96.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Further, a recent study of DHP™ in a pediatric oncology intensive care unit demonstrated reductions in both air and surface contamination along with a robust safety profile. 37 In the present study, DHP™ resulted in an overall 96. Contaminated surfaces play an essential role in the transmission of pathogens via hand contamination of healthcare personnel and increase the risk for future patients occupying the rooms.…”
Section: Discussionmentioning
confidence: 99%
“…The CFUs in the air in the rooms with the DHP units also were reduced compared with the control rooms, but the difference was not statistically significant. 5…”
Section: Dry Hydrogen Peroxidementioning
confidence: 99%